2013
DOI: 10.1073/pnas.1303738110
|View full text |Cite
|
Sign up to set email alerts
|

Neisseria gonorrhoeae-derived heptose elicits an innate immune response and drives HIV-1 expression

Abstract: Clinical and epidemiological synergy exists between the globally important sexually transmitted infections, gonorrhea and HIV. Neisseria gonorrhoeae , which causes gonorrhea, is particularly adept at driving HIV-1 expression, but the molecular determinants of this relationship remain undefined. N. gonorrhoeae liberates a soluble factor that potently induces expression from the HIV-1 LTR in coinfected cluster of differentiation 4-positive (CD4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 56 publications
1
52
0
1
Order By: Relevance
“…For example, confection with Neisseria gonorrhoeae is associated with elevated concentrations of HIV-1 in the blood plasma of women 56 and in semen 57 . N. gonorrhoeae produces heptose monophosphate, which stimulates an innate immune response that results in increased nuclear factor-κB (NF-κB)-mediated transcription of the HIV-1 long terminal repeats (LTR) 58 as one mechanism that could affect the level of virus. Similarly, co-infection with herpes simplex virus 2 (HSV-2) has also been associated with elevated concentrations of HIV-1 in genital secretions (reviewed in REF.…”
Section: Transmission Bottlenecks In the Donormentioning
confidence: 99%
“…For example, confection with Neisseria gonorrhoeae is associated with elevated concentrations of HIV-1 in the blood plasma of women 56 and in semen 57 . N. gonorrhoeae produces heptose monophosphate, which stimulates an innate immune response that results in increased nuclear factor-κB (NF-κB)-mediated transcription of the HIV-1 long terminal repeats (LTR) 58 as one mechanism that could affect the level of virus. Similarly, co-infection with herpes simplex virus 2 (HSV-2) has also been associated with elevated concentrations of HIV-1 in genital secretions (reviewed in REF.…”
Section: Transmission Bottlenecks In the Donormentioning
confidence: 99%
“…Similarly, gonorrhea cases among MSM increased 14% compared to the cases among men who have sex with women only that remained stable and the proportion of cases among women that declined 13% (Kidd, Stenger, Kirkcaldy, Llata, & Weinstock, 2015). Data further show that STIs potentiate HIV acquisition and transmission (Dallabetta & Neilsen, 2005; Frye et al, 2009; Malott et al, 2013). Both RAI and IAI, as sexual positioning practices, can facilitate HIV acquisition and transmission among MSM.…”
Section: Introductionmentioning
confidence: 84%
“…Ferreira et al found that stimulation of HIV infected T-cells with TLR3, 4, or 5 ligands leads to enhanced HIV-1 replication via direct activation of HIV long terminal repeats, or by inducing secreted factors that promote HIV replication [109]. Among the pathogens suspected to contribute to HIV infection and reactivation, one player stands out - Neisseria gonorrhoeae : it was found to be highly associated with HIV infection [110] and activation of HIV expression [109,111,112]. Not only does N. gonorrhoeae drives an increase of activated CD4+ T-cells [111] and pro-inflammatory cytokines in genital epithelial cells such as IL-6, IL-8 and TNFα [109], but exposure to the pathogen directly drives HIV expression in T cells in NF-kB and AP-1 dependent manner [109,111].…”
Section: Cervicovaginal Microbiomementioning
confidence: 99%
“…Among the pathogens suspected to contribute to HIV infection and reactivation, one player stands out - Neisseria gonorrhoeae : it was found to be highly associated with HIV infection [110] and activation of HIV expression [109,111,112]. Not only does N. gonorrhoeae drives an increase of activated CD4+ T-cells [111] and pro-inflammatory cytokines in genital epithelial cells such as IL-6, IL-8 and TNFα [109], but exposure to the pathogen directly drives HIV expression in T cells in NF-kB and AP-1 dependent manner [109,111]. Malott et al showed that N. gonorrhoeae by-product heptose-monophosphate is necessary for invoking these host responses [111] (Fig.…”
Section: Cervicovaginal Microbiomementioning
confidence: 99%
See 1 more Smart Citation